Iowa RBA, September 6-9, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Two emails of Iowa RBA updates for September 6 and 9, 1999. Highlights of the updates include sightings of a Red Knot, Snowy Egret, Mississippi Kite, Red-necked Phalarope, Little Blue Heron, Marbled Godwit, and a Yellow-Crowned Night Heron. Epson - sheet feed/flatbed